Peran Komitmen Organisasi dalam Memediasi Pengaruh Kompetensi terhadap Kinerja Pegawai pada Inspektorat Kabupaten Pelalawan - Rubina, Rubina; Seswandi, Agus; Zargustin, Dedi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: his study aimed to determine the effect of competency on employee performance in the Pelalawan district inspectorate and the role of organizational commitment in mediating the relationship between these two variables. Methodology/approach: This research is quantitative research that uses cross-sectional techniques. The population in this study was Pelalawan Regency Inspectorate Employees, totaling 83 people, using total sampling. Statistical data analysis using the Smart PLS program Results: The results indicate that Competency and Organizational Commitment have a direct and significant effect on Employee Performance at the Pelalawan Regency Inspectorate. In addition, competency has a significant direct effect on employees’ organizational commitment at the Pelalawan Regency Inspectorate. Organizational Commitment is also considered capable of mediating the relationship between Competency and Employee Performance at the Pelalawan Regency Inspectorate Limitations: This research was only carried out at the Pelalawan Regency inspectorate which is a government institution so it cannot be generalized to private companies Contribution: This study can contribute to readers and anyone who wants to conduct research on organizational competence and commitment to employee performance in government institutions. Novelty: This research uses organizational commitment as a mediating variable in determining the relationship between competency and employee performance.